Surface Quality Analysis of Cutting Tool Microgeometry to Achieve Higher Durability - Hronek, Ondrej; Zetek, Miroslav; Baksa, Tomas; Adamek, Pavel (Manufacturing Technology Journal, 2018)
Mapping surface quality changes during modification of the cutting tool microgeometry and reflecting on overall quality is the main purpose of this article. A complex view of microgeometry brings together the effects of indvidual stages in the processes which increase the cutting tool properties. The main objective is to increase the durability of the cutting tool. Grinding, microgeometry modification and deposition of a thin resistant layer on the cutting tool are the basic stages during the experiment. These stages have a significant effect on microgeometry parameters. Cutting edge radius, cutting edge symmetry (K factor), roughness of chipping and clearance surfaces are parameters affected by modification processes. Changing individual microgeometry parameters determines not only the surface quality of the cutting tool, but also affects the durability and stability of the cuting process. Appropriate microgeometry modification can make the cutting process more efficient. The combination of process stages and their influence on the quality of the microgeometry of the cutting tool is the primary objective in this article.
Keywords: Cutting Edge Modification; Cutting Edge Microgeometry; Surface Quality; Cutting Tool Surface